Programa Sala do Artista Popular: um espaço de encontros, trocas e democratização de culturas - Daniel Reis (e-cadernos ces)
In recent years, the interest in the so-called folk arts has grown among many people, institutions and areas of knowledge. Some routes have shown to be relevant, such as: patrimonialisation processes; government cultural policies; (re)musealization projects; artification processes; and inclusion in certification systems, such as Geographical Indications. This text aims to provide comments on the segment of public policies of culture based on the analysis of the experience of the Sala do Artista Popular [the Popular Artist’s Room] (SAP) Program, conducted by the National Center for Folklore and Popular Culture in Rio de Janeiro. Created in the 1980s with the objectives of documenting, valuing and disseminating the popular arts in the country, SAP, as it is known, instigates us to think about questions such as: What dialogues does SAP promote in the field of the popular arts? How has it been appropriated over time and what is its timeliness? What does it say about the sudden current “harassment” of the popular arts?